Experiences of students from the African diaspora at predominantly white institutions (PWI). - Sarah M Ray (Adult Education Research Conference, 2017)
Experiences of profiling, racism and discrimination are a part of life for many students in America. Perceptions of non-white, African International students about African American students is influenced by stereotypes and inadequate historical context of Black American experiences. This qualitative study addresses Black students from various parts of the African diaspora's experiences of racism, and perceptions of race/ethnic-based biases during their educational experiences in a predominantly white institution (PWI), through semi-structured interviews.
Keywords: Racism; African Diaspora; Qualitative Research; International Students